Down‐regulation of KIAA1199/CEMIP by miR‐216a suppresses tumor invasion and metastasis in colorectal cancer. Issue 10 (2nd March 2017) - Zhang, Dejun; Zhao, Lei; Shen, Qiong; Lv, Qing; Jin, Min; Ma, Hong; Nie, Xiu; Zheng, Xiumei; Huang, Shaoyi; Zhou, Pengfei; Wu, Gang; Zhang, Tao
Abstract : Colorectal cancer is one of the major causes of death from cancer. Metastasis is the leading cause of treatment failure, in which cancer stem cells and circulating tumor cells play crucial roles. Identifying the involved metastatic biomarkers and clarifying the regulation mechanisms are of great importance for targeting tumor metastasis. In the current research, we discovered that KIAA1199, a cell‐migration inducing protein, showed higher expression in CD44+ cancer cells from metastatic compared with the paired primary tissues, and was upregulated in colorectal cancer and positively correlated with numbers and mesenchymal phenotype of circulating tumor cells, and predicted shorter progress‐free survival. Moreover, we indicated that down‐regulation of KIAA1199 suppressed migration and invasion of colorectal cancer cells in vitro, and inhibited metastasis in vivo . Furthermore, we demonstrated that KIAA1199 was one of the direct and functional targets of miR‐216a, and miR‐216a overexpression led to decreased migration and invasion of colorectal cancer cells in vitro, and inhibited metastasis in vivo . Collectively, KIAA1199 plays a critical role in maintaining an aggressive phenotype of tumor cells, and suppression of KIAA1199‐related motilities of tumor cells contributes to reduced tumor metastasis in colorectal cancer. Abstract : What's new? Metastasis is the leading cause of treatment failure in colorectal cancer (CRC). Here, the authors found that KIAA1199, a cell‐migration inducing protein, was more highly expressed in CD44+ cancer cells from metastatic CRC tissues compared with paired primary CRC tissues. KIAA1199 was up‐regulated in CRC, correlated positively with circulating tumor cells and predicted poor survival. KIAA1199 down‐regulation suppressed invasion and metastasis of CRC cells. In particular, miR‐216a directly targeted KIAA1199 and led to decreased invasion and metastasis. The data suggest that KIAA1199 plays a critical role in maintaining an aggressive phenotype and targeting KIAA1199 could reduce tumor metastasis in CRC.